Antigen Presentation by Vascular Cells - Pober, Jordan S.; Merola, Jonathan; Liu, Rebecca; Manes, Thomas D. (Frontiers in Immunology, 2017)
Antigen presentation by cells of the vessel wall may initiate rapid and localized memory immune responses in peripheral tissues. Peptide antigens displayed on major histocompatibility complex (MHC) molecules on the surface of endothelial cells (ECs) can be recognized by T cell receptors (TCRs) on circulating effector memory T cells (TEM), triggering both transendothelial migration and activation. The array of costimulatory receptors, adhesion molecules, and cytokines expressed by ECs serve to modulate T cell activation responses. While the effects of these interactions vary among species, vascular beds, and vascular segments within the same tissue, they are capable of triggering allograft rejection without direct involvement of professional antigen presenting cells (APCs) and may play a similar role in host defense against infections and in autoimmunity. Once across the endothelium, extravasating TEM then contact mural cells of the vessel wall, including pericytes (PCs) or vascular smooth muscle cells (VSMCs), that may also present antigens and provide signals that further regulate T cell responses. Collectively, these interactions provide an unexplored opportunity in which targeting of vascular cells can be used to modulate immune responses. In organ transplantation, targeting ECs with siRNA to reduce expression of MHC molecules may additionally mitigate perioperative injuries by preformed alloantibodies, further reducing the risk of graft rejection. Similarly, genetic manipulation of vascular cells to minimize antigen-dependent responses can be used to increase perfusion of tissue engineered organs without triggering rejection.